2018
DOI: 10.1111/ejn.14186
|View full text |Cite
|
Sign up to set email alerts
|

The phase of pre‐stimulus brain oscillations correlates with cross‐modal synchrony perception

Abstract: In everyday life multisensory events, such as a glass crashing on the floor, the different sensory inputs are often experienced as simultaneous, despite the sensory processing of sound and sight within the brain are temporally misaligned. This lack of cross‐modal synchrony is the unavoidable consequence of different light and sound speeds, and their different neural transmission times in the corresponding sensory pathways. Hence, cross‐modal synchrony must be reconstructed during perception. It has been sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 64 publications
1
23
0
Order By: Relevance
“…One recent study by Benedetto et al (2018) further shows that audio-visual temporal order judgments (TOJs) undergo rhythmic fluctuations (at around 7-8 Hz) time-locked to a button press action (figure 4). The modulation does not affect temporal sensitivity (precision of the judgements) but the temporal bias, i.e., whether the visual stimulus is perceived ahead or behind of the auditory stimulus (in line with the neuronal phase effects on audio-visual perceived simultaneity reported by Ikumi et al, 2018;and Kösem et al, 2014). This suggests that processing resources and\or speed may rhythmically alternate between the visual and the auditory modality and this alternation may be temporally synchronized to the ongoing motor processing.…”
Section: Multiple Clocks One Time?mentioning
confidence: 51%
“…One recent study by Benedetto et al (2018) further shows that audio-visual temporal order judgments (TOJs) undergo rhythmic fluctuations (at around 7-8 Hz) time-locked to a button press action (figure 4). The modulation does not affect temporal sensitivity (precision of the judgements) but the temporal bias, i.e., whether the visual stimulus is perceived ahead or behind of the auditory stimulus (in line with the neuronal phase effects on audio-visual perceived simultaneity reported by Ikumi et al, 2018;and Kösem et al, 2014). This suggests that processing resources and\or speed may rhythmically alternate between the visual and the auditory modality and this alternation may be temporally synchronized to the ongoing motor processing.…”
Section: Multiple Clocks One Time?mentioning
confidence: 51%
“…Interestingly, the optimal delay between flashes is correlated with the subject-specific impulse response frequency, pointing to a contribution of oscillatory reverberation to illusory visual perception. Similarly, the phase of ongoing alpha band oscillations influences crossmodal synchrony perception 24 . A phase reset of ongoing slow oscillations in unisensory areas is a likely mechanism for the modulation of activity following heteromodal input 13,25,26 .…”
Section: Discussionmentioning
confidence: 99%
“…While the ERP signals recorded before the onset of stimuli have traditionally been considered as "baseline" and not included in data analysis, there is emerging evidence to suggest that there are functional implications for pre-stimulus activity (Falkenstein, Hoormann, Christ, & Hohnsbein, 2000;Lazzaro, Gordon, Whitmont, Meares, & Clarke, 2001). The inter-trial variability of the pre-stimulus activity has been repeatedly been reported as being related to one's cognitive states (Bode et al, 2012;Ikumi, Torralba, Ruzzoli, & Soto-Faraco, 2019;Lou, Li, Philiastides, & Sajda, 2014;Polich & Kok, 1995). As the mean amplitude of the pre-stimulus period was subtracted before the analysis, our results suggest a possible contribution from the fluctuation of the baseline activity rather than its absolute amplitude.…”
Section: Discussionmentioning
confidence: 99%